Implementasi Pola Asuh Pondok Pesantren Darul Hikmah Menganti dalam Internalisasi Nilai-Nilai Religius Santri Usia Dasar - Danella Ayu Febriana Putri; Taufiqurrahman Taufiqurrahman (Ta’dib : Jurnal Pendidikan Islam, 2026)
This study analyzes the implementation of parenting patterns at Darul Hikmah Menganti Islamic Boarding School in internalizing religious values among elementary-aged students. Using a qualitative field research approach, data were collected through observation, interviews, and documentation involving caregivers, administrators, and 5th–6th grade students over three months. Findings indicate that the boarding school applies a democratic parenting pattern implemented holistically through 24-hour mentoring across six life dimensions: spiritual, physical, emotional, social, academic, and expressive. Religious value internalization occurs simultaneously through three interconnected stages-transformation, transaction, and transinternalization embedded in every daily activity. The dynamic balance between structured control and emotional warmth facilitates authentic value internalization in elementary-aged students.